Therapeutic cancer vaccines in pancreatic cancer - Wang, YuHan; Huang, Peng; Li, Chun; Tu, ShengJin; Yang, Hua (Frontiers in Immunology, 2025)
Pancreatic cancer is a leading cause of cancer-related mortality, and unfortunately, the prognosis for this stubborn tumor type has remained bleak for an extended period. Current treatment options are limited and often ineffective, highlighting the need for innovative therapeutic strategies. Research in tumor immunotherapy has advanced significantly over the past few decades, leading to numerous studies progressing to clinical evaluation. Cancer vaccines are regarded as a promising therapeutic approach for treating pancreatic cancers. Cancer vaccines offer distinct advantages, especially for patients who are unresponsive to other treatments, as they can elicit broad and long-lasting T cell responses. This review offers a thorough examination of recent preclinical and clinical results of therapeutic cancer vaccines in pancreatic cancer therapy, highlighting the recent advancements in vaccine delivery platforms. Despite ongoing clinical efforts to develop cancer vaccines, there has not been a breakthrough in clinical outcomes, primarily due to substantial challenges including the low mutation burdens, the assessment of immune responses in preclinical models, and the intrinsic resistances to cancer vaccines. By tackling these challenges, cancer vaccines can expand the possibilities of personalized immunotherapy for pancreatic cancer.